Clinical features and therapeutic outcomes of GH/TSH cosecreting pituitary adenomas: experience of a single pituitary center - Yu, Na; Duan, Lian; Hu, Fang; Yang, Shengmin; Liu, Jie; Chen, Meiping; Yao, Yong; Deng, Kan; Feng, Feng; Lian, Xin; Mao, Xinxin; Zhu, Huijuan (Frontiers in Endocrinology, 2023)
Background: Growth hormone (GH)/thyroid stimulating hormone (TSH) cosecreting pituitary adenoma (PA) is an exceedingly rare kind of plurihormonal pituitary tumor. Its clinical characteristics have rarely been reported. Objectives: This study aimed to summarize the clinical characteristics and experience of diagnosis and treatment among patients with mixed GH/TSH PAs from a single center. Methods: We retrospectively reviewed GH/TSH cosecreting PAs from 2063 patients diagnosed with GH-secreting PAs admitted to Peking Union Medical College Hospital between January 1st, 2010, and August 30th, 2022 to investigate the clinical characteristics, hormone detection, imaging findings, treatment patterns and outcomes of follow-up. We further compared these mixed adenomas with age- and sex-matched cases of GH mono-secreting PAs (GHPAs). Results: Based on the inclusion and exclusion criteria, 21 GH/TSH cosecreting PAs were included. The average age of symptom onset was 41.6 ± 14.9 years old, and delayed diagnosis occurred in 57.1% (12/21) of patients. Thyrotoxicosis was the most common complaint (10/21, 47.6%). The median inhibition rates of GH and TSH in octreotide suppression tests were 79.1% [68.8%, 82.0%] and 94.7% [88.2%, 97.0%], respectively. All these mixed PAs were macroadenomas, and 23.8% (5/21) of them were giant adenomas. Comprehensive treatment strategies comprised of two or more therapy methods were applied in 66.7% (14/21) of patients. Complete remission of both GH and TSH was accomplished in one-third of cases. In the comparison with the matched GHPA subjects, the mixed GH/TSH group presented with a higher maximum diameter of the tumor (24.0 [15.0, 36.0] mm vs. 14.7 [10.8, 23.0] mm, P = 0.005), a greater incidence of cavernous sinus invasion (57.1% vs. 23.8%, P = 0.009) and a greater difficulty of long-term remission (28.6% vs. 71.4%, P <0.001). In addition, higher occurrence rates of arrhythmia (28.6% vs. 2.4%, P = 0.004), heart enlargement (33.3% vs. 4.8%, P = 0.005) and osteopenia/osteoporosis (33.3% vs. 2.4%, P = 0.001) were observed in the mixed PA group. Conclusion: There are great challenges in the treatment and management of GH/TSH cosecreting PA. Early diagnosis, multidisciplinary therapy and careful follow-up are required to improve the prognosis of this plurihormonal PA.